Concepts of genetics - Klug, William S.; Klug, William S.; Cummings, Michael R.; Spencer, Charlotte A.; Palladino, Michael A. (Hoboken, Pearson, 2015)
Concepts of Genetics, Eleventh Edition emphasizes the fundamental ideas of genetics, while exploring modern techniques and applications of genetic analysis. The best-selling text has a strong problem-solving approach, and this edition has been extensively updated with relevant, cutting-edge coverage of emerging topics in genetics.
Appendix A-B-1-56p.; Glossary G-1-22p.; Index I-1-23p.
Keywords: Genomics; Organisms; Replication and variation; Chromosomes